Rhinosporidium seeberi: A Human Pathogen from a Novel Group of Aquatic Protistan Parasites - David N. Fredricks; Jennifer A. Jolley; Paul W. Lepp; Jon C. Kosek; David A. Relman (Emerging Infectious Diseases, 2000)
Rhinosporidium seeberi, a microorganism that can infect the mucosal surfaces of humans and animals, has been classified as a fungus on the basis of morphologic and histochemical characteristics. Using consensus polymerase chain reaction (PCR), we amplified a portion of the R. seeberi 18S rRNA gene directly from infected tissue. Analysis of the aligned sequence and inference of phylogenetic relationships showed that R. seeberi is a protist from a novel clade of parasites that infect fish and amphibians. Fluorescence in situ hybridization and R. seeberi-specific PCR showed that this unique 18S rRNA sequence is also present in other tissues infected with R. seeberi. Our data support the R. seeberi phylogeny recently suggested by another group. R. seeberi is not a classic fungus, but rather the first known human pathogen from the DRIPs clade, a novel clade of aquatic protistan parasites (Ichthyosporea).